Biofilms and Methods of Their Reproduction in the Experiment - A. D. Daudova; Yu. Z. Demina; O. V. Rubalsky; A. L. Yasenyavskaya (Антибиотики и Химиотерапия)
Isolated bacteria, their morphological, biochemical, and genetic properties are, to this day, the main object of research since the isolation of a pure culture of the pathogen by R. Koch and his formulation of the postulates reflecting the role of the microorganism in the development of infectious diseases. The pharmacokinetic and pharmacodynamic properties of compounds with potential antibacterial activity are also studied in relation to planktonic, free cells. In recent years, as knowledge accumulates and new infections and conditions involving specially organized microbial communities — biofilms — are discovered, the approach to the diagnosis and treatment of infectious diseases, especially those with a chronic course, is changing. In this regard, the improvement and development of new representative models of microbial consortia both in vitro and in vivo are extremely relevant. Along with modern research methods, this will allow us to deepen our knowledge of the patterns of formation, construction, and functioning of the microbial world in a specific ecological niche, to develop innovative approaches to the treatment of biofilm infections, and to discover new target points for the action of antimicrobial drugs, directed at a multifaceted microbial consortium instead of individual bacteria. The review presents the main approaches to reproducing biofilm infections in vitro and in vivo experiments, highlighting their advantages, disadvantages, and possible prospects for increasing the relevance and validity of the models.